2016
DOI: 10.3747/co.23.3012
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Nature of Supportive Care Needs in Lung Cancer Patients

Abstract: PurposeIn the present work, we set out to comprehensively describe the unmet supportive care and information needs of lung cancer patients. MethodsThis cross-sectional study used the Supportive Care Needs Survey Short Form 34 (34 items) and an informational needs survey (8 items). Patients with primary lung cancer in any phase of survivorship were included. Demographic data and treatment details were collected from the medical charts of participants. The unmet needs were determined overall and by domain. Univa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
58
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 30 publications
12
58
1
1
Order By: Relevance
“…Patients desire both providers and cancer treatment centres that are up-to-date with advances in the field and treat them as whole persons. Our findings regarding unmet needs and improving healthcare experiences are consistent with the literature on needs of patients with cancer 18 19 21–24. Further, our study provides an in-depth account regarding this new group of patients with cancer as they survive longer than initially anticipated.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Patients desire both providers and cancer treatment centres that are up-to-date with advances in the field and treat them as whole persons. Our findings regarding unmet needs and improving healthcare experiences are consistent with the literature on needs of patients with cancer 18 19 21–24. Further, our study provides an in-depth account regarding this new group of patients with cancer as they survive longer than initially anticipated.…”
Section: Discussionsupporting
confidence: 86%
“…The landscape of cancer care, in general, has shifted in the past few decades. What has become salient are issues related to long-term side effects and consequences of treatment, the early detection of relapse or secondary tumours and addressing patients’ unmet needs 17–19. Smith reviewed 11 qualitative and quantitative papers on the supportive care needs of patients living with different cancers and found informational support to be a significant need 18.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies, including a systematic review [ 6 ], have demonstrated supportive care needs among patients with lung cancer; however, most studies have not addressed their needs over time [ 6 8 ] or just focused on the advanced stage or palliative radiotherapy [ 9 ]. Halkett et al [ 10 ] indicated that the information needs of patients differed during various stages of treatment and recommended continually confirming the information needs of patients throughout four stages of treatment: at the initial physician consultation, at the joint development of the follow-up treatment plan, at the initial treatment, and on completion of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…As evidenced by the literature, each treatment stage requires the development of new therapeutic goals, thereby resulting in different patient information needs. In addition, examining information needs over time is important and has been recommended in several studies [ 7 8 ]. Therefore, to provide information that actually meets the needs of patients, healthcare personnel should consider the individual needs of patients and make assessments accordingly [ 13 ].…”
Section: Introductionmentioning
confidence: 99%